2018
DOI: 10.1530/rep-18-0282
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid Signaling Controlled by SRC-2 in Decidualization Revealed by Transcriptomics

Abstract: Establishment of a successful pregnancy requires not only implantation of a healthy embryo into a receptive uterus but also progesterone receptor (PGR)-dependent transformation of endometrial stromal cells (ESCs) into specialized decidual cells. Decidual cells support the developing embryo and are critical for placentation. We have previously shown that a known transcriptional coregulator of the PGR, Steroid Receptor Coactivator-2 (SRC-2), is a critical driver of endometrial decidualization in both human and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
(64 reference statements)
1
16
0
Order By: Relevance
“…Microarray analysis further revealed that SRC-2 is necessary for P4 regulation of Wnt signaling, BMP2 signaling, and ESR1 signaling [110]. The requirement of SRC-2 for decidualization was also confirmed in in vitro decidualization of human endometrial stromal cells [115], and transcriptomic analysis revealed that 50% of SRC-2-regulated genes are also regulated by PGR [116], supporting the close relationship of these factors in transcriptional regulation of the decidualization process.…”
Section: Steroid Hormone Regulation Of Endometrial Functionmentioning
confidence: 95%
“…Microarray analysis further revealed that SRC-2 is necessary for P4 regulation of Wnt signaling, BMP2 signaling, and ESR1 signaling [110]. The requirement of SRC-2 for decidualization was also confirmed in in vitro decidualization of human endometrial stromal cells [115], and transcriptomic analysis revealed that 50% of SRC-2-regulated genes are also regulated by PGR [116], supporting the close relationship of these factors in transcriptional regulation of the decidualization process.…”
Section: Steroid Hormone Regulation Of Endometrial Functionmentioning
confidence: 95%
“…As described above, stromal-derived SRC-2 has a clear modifier role in progesterone signaling processes in the endometrium that are for important embryo implantation; however, the involvement of endometrial epithelial SRC-2 in the implantation process is unknown; and finally (4) In addition to metabolic pathways, can SRC-2 control other progesterone responsive signals that are crucial for endometrial stromal cell decidualization? Recent transcriptomic and cistromic investigations have not only underscored the critical importance of SRC-2 in the full induction of the majority of known molecular mediators of progesterone during human endometrial stromal cell decidualization but have also uncovered new gene targets coregulated by SRC-2 and the PGR that may represent new lines of future investigation to understand coregulator control of early progesterone responses in the endometrium during the periimplantation period ( Szwarc et al, 2018a ).…”
Section: Modifiers Of Pgr Mediated Responses In the Endometrial Epithmentioning
confidence: 99%
“…Therefore, both SUSD2 and DLL1 may play a role in Notch signaling in the endometrium, which, importantly, is also a well-known inducer of transcription program switching in the EMT. Szwarc et al (50) revealed progesterone-mediated retinoid signaling was co-regulated by SRC-2, a Src family kinase which is also a known inducer of transcription program switching in the EMT, thereby highlighting another important parallel between these two processes. Moreover, Whitby et al (44) found Scribble expression was increased in secretory phase stromal cells, which is a key polarity determinant in epithelial cells as discussed above.…”
Section: Comparison Of Cytoskeleton Regulation Between Plasma Membranmentioning
confidence: 99%